2020
DOI: 10.1101/2020.05.02.074344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network Analysis Reveals Different Cellulose Degradation Strategies acrossTrichoderma harzianumStrains Associated with XYR1 and CRE1

Abstract: Background: Trichoderma species have attracted attention as alternative plant polysaccharide-degrading enzyme sources, among other reasons. Most Trichoderma spp., such as Trichoderma atroviride and Trichoderma harzianum, are described as mycoparasitic fungi and are widely used in agriculture as biocontrol agents. T. harzianum is also a potential candidate for hydrolytic enzyme production in which gene expression is tightly controlled. Thus, a better understanding of transcriptional regulation related to the ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 132 publications
(197 reference statements)
3
4
0
Order By: Relevance
“…In this study, we detected SVs by aligning our four genomes against T. reesei QM6a (Martinez et al, 2008); although the genomes were assembled at a scaffolding level, unlike the T. reesei QM6a reference genome that was assembled at the chromosome level, we chose to proceed with this dataset because its annotation file was available . As expected, due to phylogenetic proximity to the reference genome (Rosolen et al, 2021), Tr0711 showed the lowest number of SVs compared to that of the other strains. However, although T. atroviride is phylogenetically distant from T. reesei (Rosolen et al, 2021), Ta0020 exhibited fewer SVs than that of both T. harzianum strains, and this result might be explained by the uncertain phylogenetic position of fungi in these species (Druzhinina et al, 2010).…”
Section: Insights Into the Evolutionary Historysupporting
confidence: 77%
See 4 more Smart Citations
“…In this study, we detected SVs by aligning our four genomes against T. reesei QM6a (Martinez et al, 2008); although the genomes were assembled at a scaffolding level, unlike the T. reesei QM6a reference genome that was assembled at the chromosome level, we chose to proceed with this dataset because its annotation file was available . As expected, due to phylogenetic proximity to the reference genome (Rosolen et al, 2021), Tr0711 showed the lowest number of SVs compared to that of the other strains. However, although T. atroviride is phylogenetically distant from T. reesei (Rosolen et al, 2021), Ta0020 exhibited fewer SVs than that of both T. harzianum strains, and this result might be explained by the uncertain phylogenetic position of fungi in these species (Druzhinina et al, 2010).…”
Section: Insights Into the Evolutionary Historysupporting
confidence: 77%
“…These observations might be explained by the complex speciation process within the T. harzianum species group (Druzhinina et al, 2010); therefore, the phylogenetic position is uncertain for fungi from these species. However, the molecular identification of Th3844 and Th0179 based on the ITS and tef1 sequences has already been reported (Rosolen et al, 2021), confirming that both strains were phylogenetically close to other T. harzianum strains. Tr0711 was grouped with T. pararessei CBS 125925, and both were phylogenetically in proximity to other T. reesei strains.…”
Section: Insights Into the Evolutionary Historysupporting
confidence: 62%
See 3 more Smart Citations